2019
DOI: 10.33710/sduijes.606172
|View full text |Cite
|
Sign up to set email alerts
|

Öğretmen Adaylarının Sahip Oldukları Hoşgörü Düzeylerinin Belirlenmesi

Abstract: In this journal, research articles which reflect the survey with the results and translations that can be considered as a high scientific quality, scientific observation and review articles are published. Teachers, students and scientists who conduct research to the field (e.g. articles on pure sciences or social sciences, mathematics and technology) and in relevant sections of field education (e.g. articles on science education, social science education, mathematics education and technology education) in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 12 publications
0
6
0
2
Order By: Relevance
“…When the pre-service teachers' tolerance tendencies were examined in relation to gender, the female pre-service teachers' tolerance tendencies were found to be higher than those of the male pre-service teachers. In the study conducted by Gündüz (2019), it was also found that the female pre-service teachers tend to be more tolerant than the male pre-service teachers. In their study, Büyükkaragöz and Kesici (1998) found that the teachers' tolerance and democracy attitudes vary significantly by gender in favour of the female teachers.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…When the pre-service teachers' tolerance tendencies were examined in relation to gender, the female pre-service teachers' tolerance tendencies were found to be higher than those of the male pre-service teachers. In the study conducted by Gündüz (2019), it was also found that the female pre-service teachers tend to be more tolerant than the male pre-service teachers. In their study, Büyükkaragöz and Kesici (1998) found that the teachers' tolerance and democracy attitudes vary significantly by gender in favour of the female teachers.…”
Section: Discussionmentioning
confidence: 95%
“…When the literature is reviewed, it is seen that there are several studies investigating pre-service teachers' tolerance tendencies (Cingi & Çağlar, 2020;Gündüz, 2019;Uca, 2015;Yılmaz & Güven, 2019). There are also some studies investigating pre-service teachers' democratic tendencies (Kozikoğlu, 2017;Taneri & Özbek, 2019;Yılmaz, 2011), democratic values (Akar, İnel, & Yalçıntaş, 2017;Aladağ & Çiftçi, 2017;Çermik, 2013;Köse, Azrak, & Bayır, 2020;Oğuz, 2011;Yazıcı, 2011;Yılmaz, 2011;Zehir Topkaya & Yavuz, 2011), democratic attitudes (Aydemir & Aksoy, 2010;Bektaş & Kılıç, 2011;Eğilmez, Eğilmez, & Engür, 2018;Güven, Kaya, & Aslan, 2014;Gömleksiz & Çetintaş, 2011;Saracaloğlu, Uça, & Baydilek, 2013;Taş, 2018;Toptaş & Elkatmış, 2015;Yiğit & Çolak, 2010).…”
Section: Democratic Tendencymentioning
confidence: 99%
“…Hoşgörünün yaygınlaşması toplumun siyasi, ekonomik, kültürel ve eğitim gibi bütün katmanlarını ilgilendirmektedir. Toplumun gelişimi bu katmanları oluşturan bireylerin birbirlerine hoşgörü ile yaklaşmalarına bağlıdır (Gündüz, 2019;Widmalm, 2005).…”
Section: Asla Ulaşamayacağı Ve Eline Geçmeyecek Bir şEydir;unclassified
“…Individuals need to have some values in order to be happy in the society they live in (Gündüz, 2019).…”
Section: Introductionmentioning
confidence: 99%